2023
DOI: 10.1021/acs.jpcc.3c00367
|View full text |Cite
|
Sign up to set email alerts
|

Ultrasensitive Refractive Index Sensing Based on Hybrid High-Q Metasurfaces

Abstract: High sensitivity and a large quality factor (Q) are two desirable goals to achieve a high figure of merit (FoM) in refractive index (RI) sensing. However, simultaneously satisfying these two goals is challenging. Herein, we propose a new class of hybrid high-Q metasurfaces, which are dielectric arrays standing on a Au plasmonic nanofilm, possessing the advantages of both high RI sensitivity and a large Q. The hybrid metasurface can support the plasmon-coupled lattice mode, which has extremely narrow full width… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2

Citation Types

0
2
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
3

Relationship

0
3

Authors

Journals

citations
Cited by 3 publications
(3 citation statements)
references
References 51 publications
0
2
0
Order By: Relevance
“…Conversely, dielectric nanostructures enable extremely sharp resonances due to the decreased loss of material. Nevertheless, the majority of their electromagnetic energy is confined within the structure, resulting in limited sensitivities compared to metallic nanostructures. To overcome these limitations, hybrid nanostructures combining features of metals and dielectrics (plasma and photon) have been proposed, which are able to integrate the high sensitivity of metals and the high Q factor of dielectrics, thereby endowing biosensors with high figures of merit (FOMs). …”
Section: Introductionmentioning
confidence: 99%
“…Conversely, dielectric nanostructures enable extremely sharp resonances due to the decreased loss of material. Nevertheless, the majority of their electromagnetic energy is confined within the structure, resulting in limited sensitivities compared to metallic nanostructures. To overcome these limitations, hybrid nanostructures combining features of metals and dielectrics (plasma and photon) have been proposed, which are able to integrate the high sensitivity of metals and the high Q factor of dielectrics, thereby endowing biosensors with high figures of merit (FOMs). …”
Section: Introductionmentioning
confidence: 99%
“…In recent years, optical sensors using nanomaterials have been actively developed to quickly, sensitively, and specifically identify targets. Nanomaterials also have many useful properties relative to volume, such as a large surface area, a small size, a quantum confinement effect, high surface reactivity, and improved magnetic/electrical/optical properties, which can be appropriately adjusted and applied to optical sensors [47][48][49][50]. In this review, we summarize the components, structures, and principles of LFAs and present recent advances in LFAs for detecting viral proteins by dividing methods used from 2019 to 2024 into colorimetric, fluorescence, and SERS methods.…”
Section: Introductionmentioning
confidence: 99%
“…Owing to the low loss and high Q factor, refractive index sensors based on all-dielectric BIC metasurface also possess good biocompatibility, compatibility with CMOS process, and the ability to integrate with microfluidic technology. Therefore, numerous studies have been reported in recent years on enhanced refractive index sensors based on BIC. These studies mainly focus on the design, construction, or optimization of a high- Q BIC resonant structure to enhance the sensing performance, for example, the crescent BIC metasurface, nanogap-enhanced BIC structures, dielectric metal hybrid BIC metasurface, and zigzag elliptical structure arrays, among others. However, the refractive index sensitivity achieved via these enhanced designs is generally in the range of tens to hundreds of nm/RIU, which is nearly 2 orders of magnitude lower than that of refractive index sensors based on the metal substrate, such as plasmonic sensors , and hyperbolic metamaterial sensors, significantly limiting the application of BIC and the entire all-dielectric metasurface in ultrahigh sensitive refractive index sensing.…”
mentioning
confidence: 99%